A Contribution to the Study of Prehistory of the Island of Dugi Otok (Archaeologia Adriatica, 2009)
This paper presents a grave from the site of Zdrakovac situated between Malo and Velo Jezero (small and big lake) near Žman on the island of Dugi Otok. The grave which was partially devastated by vegetation, animals and atmospheric agents was discovered by chance in 1998, and it was fully explored in 2009. Grave construction did not consist of a classical cist with regular vertically placed stone slabs. Terrain configuration has been partially used so that the source rock served as one longer side of the grave, whereas on the other side there is a larger stone with two narrow vertical stones in its extension. South-eastern shorter side of the grave consists of a vertically placed massive stone slab. The remaining side of the grave has not been determined on the opposite side as there is no evident stone architecture but only concentration of smaller stones. The cover is massive. A female person who died in her thirties was buried in the grave, most likely in a crouched position. Several ceramic and metal objects were found in the grave. Most objects were made of bronze, mostly representing jewelry and parts of attire which are usual finds in Liburnian graves. Grave goods include small ceramic vessel and spools, as well as probably iron objects whose function is difficult to determine due to poor state of preservation. Several sea pebbles were also found. Typological analysis of rich grave inventory shows that the objects laid next to the deceased person in this grave were produced and used during the 6th and 5th centuries BC. The youngest grave goods date this burial to the mid-5th century BC, or its latter half, corresponding to the fourth phase of the Liburnian culture. This grave is important because it indicates that there was a community in this region which communicated and participated in trade with other regions in the 5th century BC, which is attested by the first object that is definitely imported to the region of Dugi Otok. Furthermore, it was discovered that burials in the Iron Age took place not only under burial mounds, but also in flat graves which was a common practice in the entire Liburnian region, previously not confirmed on this island. On the basis of another massive cover, and a tumulus in the immediate vicinity of the grave, it is reasonable to assume that there was a necropolis belonging to occasionally inhabited hill-fort of Zarubinjak or a supposed settlement without hill-fort characteristics with visible remains of dry-stone wall houses on the slopes of the Zdrakovac ridge.
Keywords: Iron Age; Zdrakovac; island of Dugi Otok; Liburnians; grave